Active and Reactive Power Control of a Dual Stator Induction Machine (DSIM) using PI Controllers - Fatma Lounas; Salah Haddad; Nacereddine Benamrouche (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
In this paper, we present the active and reactive power control of a Dual Stator Induction Generator (DSIG).  Contrary to the Doubly Fed Induction Generator (DFIG), which is controlled by its rotor and which delivers power from its stator, in the DSIG, one of the two stator windings plays the role of control winding and the other plays that of the power winding. The aim of this article is to establish, using some simplifying assumptions, the relationships between the active and the reactive powers delivered from the power winding and the voltages applied at its control winding terminals. Based on these relationships, a functional diagram is built and the active and reactive power regulators are synthesized. A model of the controlled DSIG is implemented under MATLAB-Simulink environment and the simulation results showed the feasibility and the performances of the developed control laws.